Chemical Approaches to Synthetic Drug Delivery Systems for Systemic Applications. Issue 49 (26th October 2022) - Braatz, Daniel; Cherri, Mariam; Tully, Michael; Dimde, Mathias; Ma, Guoxin; Mohammadifar, Ehsan; Reisbeck, Felix; Ahmadi, Vahid; Schirner, Michael; Haag, Rainer
Abstract: Poor water solubility and low bioavailability of active pharmaceutical ingredients (APIs) are major causes of friction in the pharmaceutical industry and represent a formidable hurdle for pharmaceutical drug development. Drug delivery remains the major challenge for the application of new small‐molecule drugs as well as biopharmaceuticals. The three challenges for synthetic delivery systems are: (i) controlling drug distribution and clearance in the blood; (ii) solubilizing poorly water‐soluble agents, and (iii) selectively targeting specific tissues. Although several polymer‐based systems have addressed the first two demands and have been translated into clinical practice, no targeted synthetic drug delivery system has reached the market. This Review is designed to provide a background on the challenges and requirements for the design and translation of new polymer‐based delivery systems. This report will focus on chemical approaches to drug delivery for systemic applications. Abstract : Over 100 years after Paul Ehrlich's vision of the "magic bullet", the major challenges in drug delivery remain unchanged: 1) controlling pharmacokinetic and biodistribution drug distribution and clearance in the blood; 2) solubilizing hydrophobic agents, and 3) selectively targeting specific tissues. This Review describes new alternatives for synthetic drug delivery systems for systemic applications.